Analisis Perhitungan Harga Pokok Produksi Menggunakan Metode Full Costing Untuk Menentukan Harga Jual Pada Usaha Tahu Bapak Junaidi - Putri Agustina; Tiara Titis Indah Sari; Hadli Lidya Rikayana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the production cost recording system and compare the calculation of the Cost of Goods Manufactured (COGM) between the method applied by Mr. Junaidi's Tofu Business and the full costing method. MSMEs play a strategic role in the national economy, but often face obstacles in financial management and cost calculation accuracy. Mr. Junaidi's Tofu Business in Tanjungpinang has been calculating COGM simply by including only raw material costs and direct labor costs, without fully accounting for factory overhead costs such as equipment depreciation, electricity, and fuel. This results in inaccuracies in determining selling prices and potential hidden losses. The research method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews with the business owner, direct observation of the production process, and documentation of simple financial records. The results show a significant difference between the COGM calculation according to the business owner and the full costing method. In July, August, and September, the COGM per unit using the full costing method was much higher because it included all components of production costs, both fixed and variable. This difference indicates the presence of previously unidentified overhead costs. The implementation of the full costing method provides a more realistic and accurate cost picture, thus helping business owners set the right selling price to ensure business sustainability and optimal profit.